The adaptive learning community environment: modifying the physical classroom to foster creativity in 4th and 5th grade gifted students - Souza, Kolia (Kansas State University, 2016)
The purpose of the research study was to explore the role that the physical classroom environment plays in fostering student creativity in the combined fourth and fifth grade USD 475 gifted program. The research focused on answering the primary research question: Does the proposed environmental modification of the physical classroom foster creative behaviors in students? Secondary research questions included: 1) How does function-based classroom design affect both students and the classroom teacher in terms of creative process? 2) How does adaptability of the designed classroom environment affect both students and the classroom teacher in terms of creative process? A review of the literature led to the development of the author’s Framework for the Modification of Creative Learning Community Physical Environments. The study utilized a two-phase, experimental embedded research design that assessed the effects of an environmental modification to the physical classroom. Quantitative data collection methods included an environmental assessment and student survey utilizing a Likert scale. Qualitative data collection methods included participation observation, video observation, expert interviews, and open-ended student survey questions. The study found that the environmental modification of the physical classroom produced precursory creative behaviors in students. The emergent themes from the data analysis included facilitative physical environment, increased environmental acuity, leadership and self-esteem development, and improved teacher classroom management – all attributes found to be conducive to creativity development. These findings suggest further development of similar in-depth studies across a greater diversity of classroom learning environments is needed to establish reliability of the Framework for the Modification of Creative Learning Community Physical Environments.
Keywords: Physical environment; Learning community; Adaptive environment; Elementary school